Requirements Change Management Using Agile Methods and Dev-Ops Team Management: An Article Review - Alsharari Abdullah Sabih D , Wan Mohd Nazmee Wan Zainon , Sukumar Letchmunan , Alsharari Mohammed Sabih D (International Journal of Advanced Science and Technology, 2020)
Software engineering experts define agile development as “the collaboration between different software engineering teams to achieve cross-functional tasks and increase the pace of software development through reducing time needed to fulfil requirements of the software. This paper review the current requirement change management in agile methods especially created for website engineering and highlight their strength and weaknesses. Besides, it will show the design of requirement change model based on agile methods that provide better requirement change management for web projects to overcome the weaknesses of the current classical agile methods, and finally we want to implement the modified requirement management model in order to evaluate the effectiveness of the proposed model. Additionally, this study examines a modified version of evaluation framework that assist in monitoring the Dev-Ops effects on performance metrics; this framework proposes the use of different SE techniques such as slicing technique at the source code level and pipeline tasking development paradigm. We use a systematic review method to answer our aim to capture the current state of the art in Agile RCM as well as the role of Dev-Ops team style in improving the quality of Agile SE modeling. Then we define requirements for pattern and model then we create a model to evaluate against predefined requirements.